Elitism in Glass Onion: A Knives Out Mystery (2022) - Nabila Ardiningrum; Devani Warsito; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study looks at the worldwide issue of elitism. It takes a critical view of elitism without making it seem better than it is, as shown in the film Glass Onion: A Knives Out Mystery. The aim of this study is to examine how elitism is reflected in the dialogue and to show how the fictional world is connected to the real world. Film analysis through a social realism approach is linked to real social structure. By combining social realism with Pierre Bourdieu’s theory of elitism, this study introduces a new contribution to measure how social inequality is represented in the film and reflected in real-world social structures. This will be based on the theory by Pierre Bordieu, using a descriptive qualitative analysis. The data collection involved watching the movie three times to extract all relevant dialogues before conducting the analysis. The data set comprises 42 cases total, split into 9 cases in the Habitus framework, 6 cases in the Field framework, and 5 cases in the Cultural Capital framework, 9 Social Capital framework, 6 Economic Capital framework, 7 Symbolic Capital framework. This study provides an interpretation of elitism in the film and demonstrates the application of social realism to media reflections of real social hierarchies. This phenomenon is believed to create an imbalance of power, resulting in corruption and the potential for social exclusion and resentment.